Training Personalization for Operators of Complex Equipment. (13th May 2015) - Petukhov, Igor; Steshina, Liudmila
Abstract: The efficiency of complex technological equipment operators depends on many factors such as a development level of professionally important qualities, skills, professional experience, etc. Therefore, it is critical to define the attainment level of trainees and to assess the possibility of their permit to professional activity at the stage of training. The paper deals with a new assessment method of operators' attainment level and offers an approach for determination of an individual training path. In this connection the model of vocational aptitude on the basis of fuzzy logic was developed, this model allows to assess the integral level of the vocational aptitude and define the professionally important qualities (PIQs) to be developed. The professionally important qualities are differentiated into developing, conventionally developing and undeveloping ones. Such differentiation enables to form the quality functional of training in the manner that provides development of the developing PIQs and compensation of the undeveloping PIQs. The formation of a rule base for a certain operator's activity is performed by using special methods of expert assessment for each case. It allows to transfer the general vocational aptitude model to the specific spheres of operators' labour. A special complex of methodology and hardware&software for measurement and assessment of PIQs has been developed for a practical application of the abovementioned method. For assessment of PIQs the following techniques are used: the quality assessment of a hand-eye tracking, a hand-eye coordination, response, an ability to sensory analysis, the examination of cognitive characteristics and peculiarities of the nervous system of trainees. The developed assessment system was used in the experimental investigations of the vocational aptitude of operators of transport-technological machines in the Interregional Forestry Resource Centre. It was found out that a choice of an individual training path based on the results of the assessment system under discussion provides improvement of training effectiveness and further development of professional skills.